Impacts of temperature and selected chemical digestion methods on microplastic particles. (12th October 2017) - Munno, Keenan; Helm, Paul A.; Jackson, Donald A.; Rochman, Chelsea; Sims, Alina
Abstract: Alkaline and wet peroxide oxidation chemical digestion techniques used to extract microplastics from organic matrices were assessed for recoveries and for impacts on ability to identify polymer types. Methods using wet peroxide oxidation generated enough heat to result in the complete loss of some types of microplastic particles, and boiling tests confirmed that temperatures >70 °C were responsible for the losses. Fourier transform infrared spectroscopy (FT‐IR) confirmed minimal alteration of the recovered polymers by the applied methods. Environ Toxicol Chem 2018;37:91–98. © 2017 SETAC